Transcriptomic screen for DIS3, DIS3L1 and DIS3L2-associated functional networks in colorectal cancer - Costa, Paulo J. da (2017)
The final step of eukaryotic mRNA degradation proceeds in either a 5’-3’ direction, catalyzed by XRN1, or in a 3’-5’ direction catalyzed by DIS3, DIS3L1 (the catalytic subunits of the exosome) and/or DIS3L2 (exosome-independent). Important findings over the last years have shed a new light onto the mechanistic details of RNA degradation by these exoribonucleases. In addition, it has been shown that they are involved in growth, mitotic control and important human diseases, including cancer. In this work, we aim to analyze how DIS3, DIS3L1 and DIS3L2 regulate the human transcriptome, and how their functional interactions modulate the transcriptional reprogramming of colorectal cancer cells. Each one of these nucleases was depleted by RNA interference in HeLa cells and levels of several endogenous targets was monitored by RT-qPCR. Our results show that these exoribonucleases are target specific and not directly involved in any known mRNA decay mechanisms such as nonsense-mediated decay (NMD). However, we do not know yet what defines such target preference. In parallel, our bioinformatics analysis of available transcriptomic data from cells depleted of DIS3L1, DIS3L2, XRN1 or UPF1 (which has a central role in NMD) has shown some, but not full, redundancy among the transcripts regulated by these nucleases, which supports our experimental data. Presently, we are exploring the mechanism through which DIS3L2 is involved in NMD and how it modulates the expression of NMD targets.